PENGARUH GREEN MARKETING, PERSEPSI HARGA DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA PT. KARYA PAK OLES TOKCER DI DENPASAR - I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Purchasing decisions are intentional behavior based on desires when consumers consciously choose one of the existing actions, so in this case marketers must understand how consumers actually make purchasing decisions. This study aims to analyze and obtain empirical evidence of the effect of green marketing, price perception and electronic word of mouth on purchasing decisions at PT. Karya Pak Oles tokcer in Denpasar. The population in this study were all consumers at PT. Karya Pak Oles tokcer in Denpasar. The sample size is 100 respondents, taken using non probability sampling method, namely purposive sampling technique. Data were collected using a questionnaire. The analysis technique used is multiple linear regression analysis with the help of SPSS 22. The results showed that Green Marketing, Price Perception and Electronic Word Of Mouth had a positive and significant effect on purchasing decisions at PT. Karya Pak Oles Tokcer in Denpasar.